Experiences of mothers having preterm infants admitted in neonatal intensive care unit: a qualitative study - Acharya, Sabitri; Bhandari, Sharmila; Bhattarai, Sigma; Gaire, Hari (Journal of Chitwan Medical College, 2021)
Background: Mothers of preterm infants begin their journey of motherhood in stressful, highly medicalized environment of Neonatal Intensive Care Unit which influences variety of factors. The objective of study was to explore experiences of mothers having preterm infants admitted in NICU. Methods: Qualitative phenomenological study design was used and total of nine mothers having preterm infants were selected purposively from NICU unit of Universal College of Medical Sciences, Teaching Hospital. Data was collected using in-depth interview guidelines and analyzed using Colaizzi’s steps. Results: Six themes were emerged after analysis i.e. experiences of holding a premature baby for first time, emotional experiences, familial experiences, mother-child bonding, interaction with NICU staffs and coping strategies adopted during hospital stay. Mothers experienced contradictory emotions while holding their preterm for first time. They felt emotional detachment due to the emergency NICU admission. Mothers were anxious about unpredictable life span of baby and blamed themselves for early delivery. Although they faced economic hardship for prolonged NICU stay, they received familial support for financial expenses. During their visit to NICU, mothers felt health professionals to be supportive. To deal with these emotions, mothers adopted coping strategies like acceptance of the situation, devotion towards god, attachment with family. Conclusions: Mothers were unprepared about the birth of baby so early. So, they experienced problems like emotional detachment, and economic hardship due to emergency NICU admission. Hence, health professionals need to pay more attention to reduce anxiety of mothers by providing continuous communication about baby’s progress.